Imaging and Management of Internal Mammary Lymph Nodes. Issue 6 (13th August 2020) - Samreen, Naziya; Dhage, Shubhada; Gerber, Naamit Kurshan; Chacko, Celin; Lee, Cindy S
Abstract: Internal mammary lymph nodes (IMLNs) account for approximately 10%–40% of the lymphatic drainage of the breast. Internal mammary lymph nodes measuring up to 10 mm are commonly seen on high-risk screening breast MRI examinations in patients without breast cancer and are considered benign if no other suspicious findings are present. Benign IMLNs demonstrate a fatty hilum, lobular or oval shape, and circumscribed margins without evidence of central necrosis, cortical thickening, or loss of fatty hilum. In patients with breast cancer, IMLN involvement can alter clinical stage and treatment planning. The incidence of IMLN metastases detected on US, CT, MRI, and PET-CT ranges from 10%–16%, with MRI and PET-CT demonstrating the highest sensitivities. Although there are no well-defined imaging criteria in the eighth edition of the American Joint Committee on Cancer Staging Manual for Breast Cancer, a long-axis measurement of ≥ 5 mm is suggested as a guideline to differentiate benign versus malignant IMLNs in patients with newly diagnosed breast cancer. Abnormal morphology such as loss of fatty hilum, irregular shape, and rounded appearance (which can be quantified by a short-axis/long-axis length ratio greater than 0.5) also raises suspicion for IMLN metastases. MRI and PET-CT have good sensitivity and specificity for the detection of IMLN metastases, but fluorodeoxyglucose avidity can be seen in both benign conditions and metastatic disease. US is helpful for staging, and US-guided fine-needle aspiration can be performed in cases of suspected IMLN metastasis. Management of suspicious IMLNs identified on imaging is typically with chemotherapy and radiation, as surgical excision does not provide survival benefit and is performed only in rare cases.